2012
DOI: 10.3354/ab00481
|View full text |Cite
|
Sign up to set email alerts
|

Trophic model of the subtropical headwater stream habitat of Formosan landlocked salmon Oncorhynchus formosanus 

Abstract: Using the Ecopath approach and a network analysis, a mass-balance trophic model was constructed to analyze the structure and energy flows of a high-altitude subtropical headwater stream, Chichiawan Stream, the only habitat of the Critically Endangered Formosan landlocked salmon Oncorhynchus formosanus. Natural abundances of carbon and nitrogen isotopes (δ 13 C and δ 15 N) were used as a complementary method to stomach content analysis to trace food sources of consumers in the stream. Riparian C 3 plants were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…The original long term ecological research in Wuling area is a bimonthly investigation, from 7:30 to 19:30, we set up and retreat multiple ecological collecting traps [7] of the study area is situated at 24˚23'N, 121˚18'E and denoted both in Figure 1 and in the text as well according to our previous work [8].…”
Section: Methodsmentioning
confidence: 99%
“…The original long term ecological research in Wuling area is a bimonthly investigation, from 7:30 to 19:30, we set up and retreat multiple ecological collecting traps [7] of the study area is situated at 24˚23'N, 121˚18'E and denoted both in Figure 1 and in the text as well according to our previous work [8].…”
Section: Methodsmentioning
confidence: 99%
“…Such changes are a threat to national security, the livelihood of residents, tourism and sightseeing, ecosystem preservation and sustainable development of fishery [35]. In addition, warm water temperatures related to climate change is well documented to increase the rate of coral bleaching [36].…”
Section: Coral Bleachingmentioning
confidence: 99%
“…Due to the Formosan salmon's critically endangered status (Chung et al 2008), there is an urgent need to identify the energy sources supporting the stream food web. Lin et al (2012) identified mayfly grazers as an important food source for the Formosan salmon in the stream. Nevertheless, the diet of mayfly grazers in the Chichiawan Stream is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Autochthonous algae may be more important than allochthonous organic matters to stream consumers in tropical forested headwater streams (March and Pringle 2003). An open forest canopy can lead to autochthonous algae becoming the dominant food source for herbivores in rainforest streams (Brito et al 2006) and tropical Asia (Salas and Dudgeon 2001;Mantel et al 2004;Yam and Dudgeon 2005;Lin et al 2012). Autochthonous algae are the main energy source in some shaded tropical headwater streams (Mantel et al 2004;Lau et al 2008;2009;Li and Dudgeon 2008).…”
Section: Introductionmentioning
confidence: 99%